If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1134 = 6(x + 16) Reorder the terms: 1134 = 6(16 + x) 1134 = (16 * 6 + x * 6) 1134 = (96 + 6x) Solving 1134 = 96 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 1134 + -6x = 96 + 6x + -6x Combine like terms: 6x + -6x = 0 1134 + -6x = 96 + 0 1134 + -6x = 96 Add '-1134' to each side of the equation. 1134 + -1134 + -6x = 96 + -1134 Combine like terms: 1134 + -1134 = 0 0 + -6x = 96 + -1134 -6x = 96 + -1134 Combine like terms: 96 + -1134 = -1038 -6x = -1038 Divide each side by '-6'. x = 173 Simplifying x = 173
| x(x)-12x=-8 | | 4m+7(3m-8)= | | (2+x)(x)(3)=240 | | -.3p-2.1=-3.6 | | 3x(x)+14x-5=0 | | (4200*2/3)6 | | -2x+7(0)=11 | | 2x+4=2x+3(-1x+2) | | 25x=5x-20 | | 2(n-2)=4n+6 | | 2x+3-20=500 | | 1.5x(6-4)= | | 3a=7c | | 2x+4=2x+3(-x+2) | | 500=100+3n | | 24n+72=288 | | log[2](3x+2)=log[3](12x+3) | | x(x)+7x-5=0 | | f(x)=2x^2+7x-1 | | s^2-13st-30t^2=0 | | 1.5x(6-4)=3 | | -7c-8(9-6c)= | | x(x)+16x+39=0 | | 5+2y=7 | | 6y-13=55 | | 8(y+9)=7y-3 | | solven+(n+1)+(n+2)=54 | | 25-n/2=10 | | 3(-1)-2(1/2) | | .2(-10x+25)=3x(-3-4) | | x^3+17x^2+41x+3=0 | | 25x-28=3x-10 |